Arguing About Arguing with Arguments: Replies to my Critics - Siegel, Harvey (Informal Logic, 2024)
I am most grateful to the editors of Informal Logic for their willingness to publish my absurdly long paper (Siegel 2023a) in its entirety, and for organizing the four commentaries published along with it. I am grateful as well to Bart Garssen, Andrew Aberdein, Paula Olmos and Christoph Lumer for their insightful and challenging discussions. In what follows I respond to their criticisms and suggestions in the order in which they appear in the journal.